Effect of prostaglandin F2alpha, oxytocin and butylated hydroxytoluene on fertility of crossbred (HF x Hariana) bull spermatozoa - ARANGASAMY, A; SINGH, L P; ANSARI, M R; RAWAL, C V S; GUPTA, O P (The Indian Journal of Animal Reproduction, 2023)
Semen samples collected from two crossbred bulls (HF x Hariana) were diluted in tris with three combinationsofadditives i.e., prostaglandin F ..,a (PGF2alpha ) ( 1.5 ng/ml), oxytocin (0.1 unit/ml) and.butylated hydroxytoluene (~~T)(2 mM/ml) and frozen in liquid nitrogen .-A total number of 176 oestrus cows were inseminated with all the additivestreated and control semen samples, the pregnancy diagnosis was carried out 50-60 days post insemination. Theresults, revealed overall conception rate 40.48% 48.28% 42 .31% and 42.91% in control, PGF2alpha, oxytocin and BHTtreated groups. No significant difference was observed among the treated groups separately. However. the conceptionrate was higher with PGF 2alpha treated semen when compared to control.
Keywords: Bull; spermatozoa; conception rate; PGF2alpha; oxytocin; BHT